Gambaran Perilaku Ibu Tentang Pencegahan Pneumonia Pada Anak Balita Di Wilayah Kerja Puskesmas Mekar Kecamatan Kadia Kota Kendari Tahun 2023 - Irmasari Irmasari; Hartati Bahar; Zainab Hikmawati (Pusat Riset dan Inovasi Nasional, 2024)
Pneumonia is wrong One tract infection acute respiratory infection caused by microorganisms in respiratory system starting from the nose, ears, larynx, trachea, bronchus, bronchioles, up to the lungs , which lasts not enough more than 14 days . One of the supporting factors in preventing pneumonia in children under five is the behavior of mothers of toddlers . Forms of maternal behavior patterns that can be implemented in preventing pneumonia, especially at home, include : give exclusive breast milk for the first six months, give vaccines in baby new born on the first year of birth , keep the environment clean and get the child used to living a healthy life . Objective study This For know description behavior Mother about prevention of pneumonia in child toddler . Type study This is Quantitative research using descriptive methods . The population of this study is all mothers who have children under five who are recorded in the register book in the work area of the Mekar Health Center, Kendari City in 2023. as much 1,226 respondents , sample in study This is as big as 92 respondents . The retrieval technique is carried out with random sampling technique or Cluster Random Sampling . Results study appointment that Behavior Mother about prevention of pneumonia in child toddler , respondent with own knowledge which is sufficient as much as 83.70 %, own positive attitude as much as 65.22%, own good actions amounted to 51.09%, own respondents had easy access to information with as many as 75.00 % And own 84.78% of respondents had easy access to health services , In the Work Area Public health center Blossom Subdistrict Head of Kendari City Year 2023.